1983
DOI: 10.1111/j.1365-2621.1983.tb14837.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat and Hydrogenation on Cyclopropenoid Fatty Acid Composition of Baobab (Adansonia Suarezensis) Seed Oil

Abstract: The seeds of the baobab Adansonia suarenzensis (Bombacaceae) contain 46.2% oil used for cooking by the malagasy population. This oil gives a positive Halphen test showing the presence of cyclopropenoic fatty acids (CPEFA). Composition analysis of derivatized fatty acid methyl esters was done by gas‐liquid chromatography (GLC). The A. suarenzensis seed oil contains mainly palmitic (46%) stearic (3.5%) oleic (21%) and linolenic (12%) acids. Effect of heat on CPEFA content of boabab oil was studied at 133°C and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
2
8
2
Order By: Relevance
“…Previous studies, some of which are old have shown that baobab seed oils contain saturated (particularly, palmitic acid) and unsaturated fatty acids (especially oleic, and linoleic acids). The proportions of palmitic, oleic and linoleic acids vary respectively between 19 and 47%, 13 and 43%, and 12 and 33% depending on the species .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies, some of which are old have shown that baobab seed oils contain saturated (particularly, palmitic acid) and unsaturated fatty acids (especially oleic, and linoleic acids). The proportions of palmitic, oleic and linoleic acids vary respectively between 19 and 47%, 13 and 43%, and 12 and 33% depending on the species .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, some of which are old have shown that baobab seed oils contain saturated (particularly, palmitic acid) and unsaturated fatty acids (especially oleic, and linoleic acids). The proportions of palmitic, oleic and linoleic acids vary respectively between 19 and 47%, 13 and 43%, and 12 and 33% depending on the species . These oils also contain cyclopropenic fatty acids such as sterculic acid (19: CE or 9,10‐methyleneoctadec‐9‐enoic acid) and malvalic acid (18: EC or 8,9‐methyleneheptadec‐8‐enoic acid), the content of which varies from 4 to 31% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the health concerns, vegetable oils containing CPE-FAs need to be treated with high temperature or hydrogenation before consumption (16). As a result, processing costs are increased whereas transfatty acids are also produced by the hydrogenation.…”
mentioning
confidence: 99%
“…The presence of malvalic acid was established by GLC of the fatty acid methyl esters before and after AgNO 3 /methanol rearrangement and by direct comparison with the cyclopropenoic fatty acids of Hibiscus syriacus and Althaea officinalis (Malvaceae), including their rearrangement products. Both the GLC behavior of intact malvalic acid methyl ester and the formation (and GLC) of the various degradation and rearrangement products obtained from malvalic and other cyclopropenoic fatty acid methyl esters are well known and have been described repeatedly in the relevant literature (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%